The Anthropological Code of Delia Owens’ Novel Where the Crawdads Sing and Its Film Adaptation. - Тичініна, Альона; Нікоряк, Наталія; Матійчак, Альона (Чернівці : Чернівец. нац. ун-т. ім. Ю. Федьковича, 2026)
The article analyzes the anthropological code in the novel "Where the Crawdads Sing" by D. Owens and its film adaptation by O. Newman. Owens’ text is examined in the poetical perspective of econarrative. The study outlines anthropological principles of research, interpreting a person, her multifaceted essence, and interaction with the world (people, nature, things). "Where the Crawdads Sing" is analyzed through the prism of the author's autobiographical experience, which shapes the novel's and film's multi-vector problematics and the hermeneutics of the idea manifested in the title's poetics. In particular, the themes of survival, loneliness, children's bullying, abusive relationships, racial segregation, the issue of otherness, post-traumatic stress syndrome, learning, creativity, and love are clearly outlined. Moreover, the problem of interaction between man and nature is confocal. Accordingly, anthropological codes are most clearly manifested in the plane of imagery and tropology, both in the novel and in the film. The chronotopic image of the marsh is a central argument for the specific econarrative, since the order of nature appears as an axiological criterion (model) for human interaction in society. The basis of the genre matrix is a whodunit, with all relevant genre codes. Genre polymorphism is argued by the implication of the features of a family novel, a love story, a social-psychological novel, a coming-of-age novel, and an econovel. However, econarrative appears as a leading narrative thread, a true ode to nature and natural man. The image of Kya is analyzed as an example of a natural person, whose communicative interaction with ecosystems is realized through her feelings and freedom.
Keywords: anthropology; genre; narrative; chronotope; film adaptation